2003
DOI: 10.1039/b300249g
|View full text |Cite
|
Sign up to set email alerts
|

ZnS–Zn nanocables and ZnS nanotubes

Abstract: ZnS-Zn nanocables and ZnS nanotubes have been synthesized by a thermochemical process in a simple and safe way. The as-prepared nanocables consist of a single crystal Zn core with a diameter of 20 nm and a polycrystalline ZnS sheath with a thickness of 8 nm. The evaporation of the Zn core leads to the formation of ZnS nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 16 publications
0
63
0
2
Order By: Relevance
“…Zinc nanowires may also be a good template to form 1D nanostructures of other important materials, such as ZnO, ZnS, and Cu. [8,9] Zinc nanowires and nanotubes with core/shell structures of Zn/ZnO and Zn/ZnS were usually prepared from ZnO [10][11][12] or ZnS [13][14][15] as precursors by a vapor-solid (VS) process. Recently, Peng et al reported the synthesis of zinc nanofibers with diameters of 50-200 nm by evaporation of pure zinc powders.…”
mentioning
confidence: 99%
“…Zinc nanowires may also be a good template to form 1D nanostructures of other important materials, such as ZnO, ZnS, and Cu. [8,9] Zinc nanowires and nanotubes with core/shell structures of Zn/ZnO and Zn/ZnS were usually prepared from ZnO [10][11][12] or ZnS [13][14][15] as precursors by a vapor-solid (VS) process. Recently, Peng et al reported the synthesis of zinc nanofibers with diameters of 50-200 nm by evaporation of pure zinc powders.…”
mentioning
confidence: 99%
“…One possible solution is to wrap nanomaterials with chemical inert protective shells. Different materials have been used to wrap ZnS NWs to form coaxial lateral nanowire heterostructures ͑LNHs͒, such as ZnS / SiO 2 , 16 ZnS / Zn, 17,18 ZnS / ZnO, 13,19 ZnS/BN, 15,20 and ZnS / SiC. 21 Among them, BN is the best protecting material due to its insulating properties and remarkable chemical inertness and thermal stability.…”
mentioning
confidence: 99%
“…Thus, synthesis of ZnS nanorods (Li and Alivisatos 2003), nanowires (Xiong et al 2004), nanotubes (Zhu et al 2003) and nanobelts (Pan et al 2001) have been reported. Several synthesis methods such as solvothermal decomposition Kedarnath et al 2007), microwave synthesis (Panda et al 2006), solution route (Zhang et al 2004), colloidal synthesis (Lu et al 2003), pyrolysis in furnace Kedarnath et al 2007), hydrothermal method (Liu et al 2005), etc., have been used for preparation of these materials.…”
Section: Introductionmentioning
confidence: 96%